2011
DOI: 10.1104/pp.111.177139
|View full text |Cite
|
Sign up to set email alerts
|

BBX32, an Arabidopsis B-Box Protein, Functions in Light Signaling by Suppressing HY5-Regulated Gene Expression and Interacting with STH2/BBX21  

Abstract: A B-box zinc finger protein, B-BOX32 (BBX32), was identified as playing a role in determining hypocotyl length during a largescale functional genomics study in Arabidopsis (Arabidopsis thaliana). Further analysis revealed that seedlings overexpressing BBX32 display elongated hypocotyls in red, far-red, and blue light, along with reduced cotyledon expansion in red light. Through comparative analysis of mutant and overexpression line phenotypes, including global expression profiling and growth curve studies, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
153
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(158 citation statements)
references
References 72 publications
2
153
0
3
Order By: Relevance
“…FHY3 binds to an FHY3 binding site and HY5 to an ACGT-containing element in the COP1 promoter, both of which seem to be required for the UV-B responsiveness of COP1 . Combinatorial regulation exerted by the interaction of other transcription factors with HY5/HYH is widely present, with negative or positive regulatory effects (Shin et al, 2007;Andronis et al, 2008;Holtan et al, 2011;Huang et al, 2012;Jiang et al, 2012;Singh et al, 2012;Gangappa et al, 2013aGangappa et al, , 2013bJing et al, 2013;Abbas et al, 2014). Moreover, HY5 interacts with the chromatin-remodeling factor PICKLE (PKL), recruiting PKL to promoters of target genes repressing the H3K27me3-repressive histone mark (Jing et al, 2013).…”
Section: Regulation Of the Hy5 Association With Chromatinmentioning
confidence: 99%
“…FHY3 binds to an FHY3 binding site and HY5 to an ACGT-containing element in the COP1 promoter, both of which seem to be required for the UV-B responsiveness of COP1 . Combinatorial regulation exerted by the interaction of other transcription factors with HY5/HYH is widely present, with negative or positive regulatory effects (Shin et al, 2007;Andronis et al, 2008;Holtan et al, 2011;Huang et al, 2012;Jiang et al, 2012;Singh et al, 2012;Gangappa et al, 2013aGangappa et al, , 2013bJing et al, 2013;Abbas et al, 2014). Moreover, HY5 interacts with the chromatin-remodeling factor PICKLE (PKL), recruiting PKL to promoters of target genes repressing the H3K27me3-repressive histone mark (Jing et al, 2013).…”
Section: Regulation Of the Hy5 Association With Chromatinmentioning
confidence: 99%
“…Elucidating both individual protein associations and complex protein interaction networks adds to the understanding of the molecular mechanisms of biological functions. Previous studies have shown that AtBBX32 plays a role in HY5-associated light signaling in A. thaliana (10) and that constitutive expression of AtBBX32 in soybean results in a consistent yield increase (14). It has been proposed that AtBBX32 functions as part of a multiprotein complex as a transcriptional accessory protein (10).…”
Section: Identification Of Interface Residues His-15 and Arg-44 In Mmentioning
confidence: 99%
“…Previous studies have shown that AtBBX32 plays a role in HY5-associated light signaling in A. thaliana (10) and that constitutive expression of AtBBX32 in soybean results in a consistent yield increase (14). It has been proposed that AtBBX32 functions as part of a multiprotein complex as a transcriptional accessory protein (10). However, no biochemical function has been definitively ascribed to the B-box motif in AtBBX32.…”
Section: Identification Of Interface Residues His-15 and Arg-44 In Mmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46] Functional description of other members of this family have uncovered roles in circadian rhythm regulation for COL1, 47 red light photomorphogenic signaling for COL3, 48 flowering control for COL5 and COL9 49,50 and negative control of light-induced genes in the dark for BBX32. 51 Sub-family IV is composed of eight members (Fig. 1).…”
Section: Bbx Protein Classificationmentioning
confidence: 99%